Students and lecturers' perspectives of MOOCs as an educational innovation for sustainable learning - Almaknunah, Luluk; Muali, Chusnul (Jurnal Inovasi Teknologi Pendidikan, 2025)
The integration of Massive Open Online Courses (MOOCs) into higher education in Indonesia continues to face significant challenges, particularly regarding their effectiveness in supporting sustainable learning. Most prior studies have predominantly focused on technical aspects such as platform usage and user participation rates. At the same time, limited attention has been given to the impact of MOOCs on long-term skill development, learner autonomy, and their formal integration into academic curricula. This study offers a novel contribution by deeply exploring the perspectives of both students and lecturers on MOOCs as an educational innovation for sustainable learning in higher education. Employing a mixed-methods approach, the research utilized the MOOC Integration Perception Scale (MIPS) for quantitative data and the MOOC Sustainability Interview Protocol (MSIP) for qualitative inquiry. A total of 120 students and 20 lecturers from diverse Indonesian universities participated as respondents. Quantitative data were analyzed using descriptive statistics and independent samples t-tests, while qualitative data were examined through thematic analysis. Findings reveal that both students and lecturers highly value the flexibility and accessibility of MOOCs, especially in overcoming geographic and temporal barriers. However, concerns remain about the lack of direct interaction and the limited provision of personalized feedback, which hinders the pedagogical depth of these platforms. This study recommends the development of blended learning models and improvements in digital infrastructure, especially in underdeveloped regions, as strategic efforts to enhance MOOC integration in higher education. Future research should adopt longitudinal approaches to assess the long-term effects of MOOCs on learning outcomes, skill development, and learner autonomy.